2019
DOI: 10.3390/md17110613
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and Angiotensin-I-Converting Enzyme (ACE)-Inhibitory Peptides from Fish as Potential Cardioprotective Compounds

Abstract: The term metabolic/cardiometabolic/insulin resistance syndrome could generally be defined as the co-occurrence of several risk factors inclusive of systemic arterial hypertension. Not only that organizations, such as the world health organization (WHO) have identified high blood pressure as one of the main risk factors of the cardiometabolic syndrome, but there is also a link between the occurrence of insulin resistance/impaired glucose tolerance and hypertension that would consequently lead to type-2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 98 publications
1
45
0
2
Order By: Relevance
“…Furthermore, a number of studies have reported antioxidant, antimicrobial and antihypertensive properties in FPH (Abachi et al 2019;V azquez et al 2019), and hence, the potential of FPH as alternative to dietary antibiotics should be explored. This will open new opportunities for the development of safe, efficient and cost-effective strategies for the prevention and alleviation of many diseases in aquaculture.…”
Section: Future Research Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a number of studies have reported antioxidant, antimicrobial and antihypertensive properties in FPH (Abachi et al 2019;V azquez et al 2019), and hence, the potential of FPH as alternative to dietary antibiotics should be explored. This will open new opportunities for the development of safe, efficient and cost-effective strategies for the prevention and alleviation of many diseases in aquaculture.…”
Section: Future Research Potentialmentioning
confidence: 99%
“…Furthermore, a number of studies have reported antioxidant, antimicrobial and antihypertensive properties in FPH (Abachi et al . 2019; Vázquez et al . 2019), and hence, the potential of FPH as alternative to dietary antibiotics should be explored.…”
Section: Future Research Potentialmentioning
confidence: 99%
“…On the basis on the evidence reported above, marine organisms attracted scientists’ interest for the potential biological activities of their primary and secondary metabolites. Terpenes, shikimates, polyketides, acetogenins, peptides, alkaloids, and many uncharacterized structures, extracted and purified from marine resources [ 9 ], showed various pharmacological activities as antioxidant [ 10 ], antibacterial [ 11 ], anticancer [ 12 ], antiviral [ 13 ], anti-inflammatory [ 14 ], antidiabetic [ 15 ], antihypertensive [ 16 ], and anticoagulant [ 17 ]. This review reports the main marine products and their derivatives, describing their antioxidant, anti-inflammatory, and neuroprotective properties.…”
Section: Introductionmentioning
confidence: 99%
“…Natural components with ACE inhibitory capacity have become a focus of hypertension treatment studies. The peptide sequence of ACE-inhibitory peptides from marine organisms with strong ACE inhibitor capacity have been studied ( Table 4 ) and their activity described [ 5 , 130 , 237 , 238 , 239 ].…”
Section: Marine-based Beneficial Moleculesmentioning
confidence: 99%